Polish-Czech borderland nodal areas as an important activation sites of cross-border connections networks - Obracaj, Piotr; Opałka, Piotr (Budownictwo i Architektura / Civil and Architectural Engineering, 2018)
In this article authors present fi ndings of their research conducted in frames of the Czech Republic - Poland cross border cooperation “Edu2Work” project “Cooperation of Czech and polish borderland schools and public institutions in the area of higher education for better chances of employability on the labor market” realized from 2013 to 2015. Scope of the research included Jesenik and Bruntal districts from Czech Republic side, as well as Nysa and Prudnik Counties from polish side. Project has been realized by the Faculty of Science/Geography of the Palacký University in Olomouc and Central Mining Institute in Katowice, under the Operational Programme of Cross Border cooperation Czech Republic – Poland 2007-2013. Authors of this article have been involved to the project as experts. The work in the project, with the participation of the students, aimed at the investigating processes existing on the borderland in six thematic areas: education, tourism, transport, networking (here: creation and compaction all communication networks and cooperation coordination), entrepreneurship, space and environment. In the article examples of some activities in the cross-border space has been presented that increase these societies integration. In result proposals of the specifi c solutions of the communication networks activation were introduced. They included identifi cation of the knot locations understood as the transfer points that should become a base for socioeconomic and cultural problems of the region.